Exploring The Role Political Culter and Government Finance on The Readness of The Adoption of IPSAS - Setu Setyawan; Lia Candra Inata (Postgraduate Program Merdeka University, 2024)
We examine the relationship between political culture and government finance on the readiness of the adoption of international public sector accounting standards (IPSAS). The data in this study is all provincial governments in Indonesia in 2016 â€“ 2022 which are used as evidence to analyze the level of readiness for IPSAS adoption. The sample selected for use in this study included 44 provincial governments. The research data were analyzed using multiple regression analysis. The results of research on political culture variables affect the readiness of IPSAS adoption in the Indonesian public sector, while government finance does not affect the readiness of IPSAS adoption. To implement IPSAS Adoption in full. This research is expected to provide consideration for policymakers regarding standard improvements leading to full IPSAS and the possibility of successful implementation. The research on the readiness of IPSAS adoption in Indonesia is an interesting thing to be studied further.Â DOI: https://doi.org/10.26905/afr.v7i1.11313